2019
DOI: 10.1074/jbc.ra119.009579
|View full text |Cite
|
Sign up to set email alerts
|

Long-term, genome-wide kinetic analysis of the effect of the circadian clock and transcription on the repair of cisplatin-DNA adducts in the mouse liver

Abstract: Edited by Patrick Sung Cisplatin is the most commonly used chemotherapeutic drug for managing solid tumors. However, toxicity and the innate or acquired resistance of cancer cells to the drug limit its usefulness. Cisplatin kills cells by forming cisplatin-DNA adducts, most commonly the Pt-d(GpG) diadduct. We recently showed that, in mice, repair of this adduct 2 h following injection is controlled by two circadian programs. 1) The circadian clock controls transcription of 2000 genes in liver and, via transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Next, repair across the sensitive and resistant cell lines were averaged. The average unit gene repair profiles in Figure 4C are similar to profiles seen in other human cell types, and in cells of other species, which show elevated TS repair which peaks near the TSS, and largely depressed non-transcribed strand (NTS) repair which peaks immediately upstream of the TSS and results from antisense transcription at the promoter (28)(29)(30)(31)(32). Figure 4C shows that overall, there is no difference in amount or pattern of genespecific repair between oxaliplatinsensitive and oxaliplatin-resistant cell lines.…”
Section: Oxaliplatin-sensitive and Oxaliplatinresistant Cell Lines Hasupporting
confidence: 67%
See 1 more Smart Citation
“…Next, repair across the sensitive and resistant cell lines were averaged. The average unit gene repair profiles in Figure 4C are similar to profiles seen in other human cell types, and in cells of other species, which show elevated TS repair which peaks near the TSS, and largely depressed non-transcribed strand (NTS) repair which peaks immediately upstream of the TSS and results from antisense transcription at the promoter (28)(29)(30)(31)(32). Figure 4C shows that overall, there is no difference in amount or pattern of genespecific repair between oxaliplatinsensitive and oxaliplatin-resistant cell lines.…”
Section: Oxaliplatin-sensitive and Oxaliplatinresistant Cell Lines Hasupporting
confidence: 67%
“…Repair patterns were visualized using the Integrated Genome Viewer from the Broad Institute. Average repair patterns for a unit gene was determined and plotted as described (31,32). Repair read counts from the transcribed strands of genes were analyzed with the DESeq2 package in R to determine genes with significant differential repair.…”
Section: Xr-seq (2728)mentioning
confidence: 99%
“…Secondly, the global repair activity is clock controlled, exhibiting the repair of circadian timing of ~8 h (Yang et al 2018). To better understand DNA repair outcome, from clinical perspective, recently, using mouse liver extracts, long-term genomewide kinetic analyses of the effect of circadian rhythm and transcription on cisplatin repair were studied at singlenucleotide resolution (Yang et al 2019). After injecting cisplatin to mouse, transcribed strand (TS) showed rhythmic repair activity of cisplatin adducts within 2 days.…”
Section: Circadian Clock Machinery: Intra-adduct Dna Lesion Removal Bmentioning
confidence: 99%
“…Their quantitative analyses determined which strand of which gene is repaired at a given time of the day for the entire mouse genome and revealed that for many genes the transcribed strand and non-transcribed strand are repaired out of phase ( Yang et al, 2018 ). Similar experiments in mice showed that transcription-driven repair is nearly complete after 2 days post-DNA damage, whereas after several weeks for repair of the non-transcribed strand and the rest of the genome ( Yang et al, 2019 ). Transcribed strand repair oscillates in rhythmically expressed genes up to 2 days post-DNA damage, and in all expressed genes, there was an increase in transcribed strand repair with time from the 5′ to 3′ end ( Yang et al, 2019 ).…”
Section: Cisplatin Modulates Dna Repair Via Circadian Genes That Causmentioning
confidence: 79%
“…Similar experiments in mice showed that transcription-driven repair is nearly complete after 2 days post-DNA damage, whereas after several weeks for repair of the non-transcribed strand and the rest of the genome ( Yang et al, 2019 ). Transcribed strand repair oscillates in rhythmically expressed genes up to 2 days post-DNA damage, and in all expressed genes, there was an increase in transcribed strand repair with time from the 5′ to 3′ end ( Yang et al, 2019 ).…”
Section: Cisplatin Modulates Dna Repair Via Circadian Genes That Causmentioning
confidence: 79%